HASIL BELAJAR SISWA PROGRAM FULL DAY SCHOOL DI SMA NEGERI KOTA PADANG (Perbandingan Antara Sekolah Yang Menerapkan Full Day School Dengan Sekolah Yang Belum Menerapkan Full Day School Pada Pembelajaran Geografi Kelas XI IPS ) - sonya marpin; syafri Anwar (JURUSAN GEOGRAFI FIS UNP, 2019)
The purpose of this research is to analyze the comparison between school that apply full day school at senior high school 4 padang with school that have not yet full day school at senior high school 3 padang in geography lerning at class XI IPS. The population of research is the students of class XI IPS in the year 2018/2019 at senior high school 4 padang and senior high school 3 padang. The sampling is used random sampling. The analysis technigue used is comparison test or t-test. Independent sample test is used to compare the two groups of mean of two different samples that apply and do not apply full day school. This research found that students’ geography learning outcomes from full day school and non full day school program did not give significant differences in learning outcomes. This can be seen in the result of t-test (42,31) which is greater than t-table (α 0,01 = 2,30 and α 0,05 = 1,67).